Bread stories: understanding the drivers of bread consumption for digital food customisation - Pantidi, Nadia; Selinas, Paris; Flintham, Martin; Baurley, Sharon; Rodden, Tom (2017)
Consumer demand for food that satisfies specific needs rather than generic mass produced food is growing. In response, the food industry is actively investigating techniques for efficient and comprehensive food customisation. Digital approaches to food customisation are starting to emerge, however, the majority is currently limited to the ingredient level thus excluding consumption drivers such as people’s practices and values around food. Using the approach of cultural probes, we identified four distinct narratives around bread consumption: the healthy bread, the fresh bread, the ethical bread, and the exceptional bread. These themes encapsulate drivers of bread consumption, which we argue can inform the design of digital food innovation platforms.